Contested substantive equality in the South African Constitution: beyond social inclusion towards systemic justice. Issue 3 (2nd September 2018) - Albertyn, Catherine
Abstract: This article briefly traces South Africa's contested archive of equality, as it emerged in the twentieth century, and identifies the different liberal egalitarian, social democratic, socialist and radical ideas of equality that are appropriated and reconstructed within different struggles. It then suggests that the equality-centred, democratic Constitution represented an important anti-colonial and anti-patriarchal achievement, but that the plasticity of equality meant that it would always be open to different interpretations by the executive and parliament, as well as by courts tasked with enforcing the Constitution. The conditions of the transition and early years of democracy saw the emergence of a social democratic/liberal egalitarian equality as the dominant political and legal, if not economic, idea, most especially in the jurisprudence of the Constitutional Court. This jurisprudence was often powerfully inclusive, but less likely to be transformative, would prefer process over substance (especially in socio-economic rights) and was better at addressing inequalities of recognition than redistribution. Although it clearly registers a commitment to substantive rather than formal equality, it also reveals the differences within substantive equality between a social democratic/liberal egalitarian model and a more transformative approach. The article identifies these differences and suggests how we might reinterpret constitutional equality within a transformative approach to better address the deep and systemic inequalities in our society. It suggests that we should move through and beyond a dignity-based concern with social inclusion and sufficiency towards an idea of systemic and material justice. It proposes that the value of equality can be developed as an idea of 'equality of condition', aligned with an idea of substantive freedom, that would better resonate with the struggles of our past and present, and suggests how the right could be subject to more transformative interpretation and application.